The Shadow of Totalitarianism : Action, Judgment, and Evil in Politics. - Burdman, Javier (Albany : State University of New York Press, 2022)
Examines the relationship of evil, action, and judgment in the work of Immanuel Kant, Hannah Arendt, and Jean-François Lyotard.
The Problem of Legitimacy and the Turn to Kant -- Critical, Political, and Reflective Judgment -- The Sublime and the Differend -- Universality as a Sublime Sign -- Conclusion -- Conclusion: Extreme Evil as a Response to Political Uncertainty -- The Eichmann Problem and Responsibility -- Ideological Extremism -- Uncertainty and Totalitarianism -- Political and Moral Judgments -- The Politics of the Lesser Evil -- Notes -- Bibliography -- Index
Description based upon print version of record.
JSTOR
Keywords: Arendt, Hannah, -- 1906-1975.; Lyotard, Jean-François, -- 1924-1998.; Kant, Immanuel, -- 1724-1804.; Arendt, Hannah, -- 1906-1975; Kant, Immanuel, -- 1724-1804; Lyotard, Jean-François, -- 1924-1998; Totalitarianism; Good and evil; Act (Philosophy); Judgment (Logic); Political science -- Philosophy; Totalitarisme; Action (Philosophie); Jugement (Logique); totalitarianism; Act (Philosophy); Good and evil; Judgment (Logic); Political science -- Philosophy; Totalitarianism